Socio Economic Factors Causing Rapid Peatlands Degradation in South Sumatra - Elisa Wildayana; M. Edi Armanto; Imron Zahri; Dessy Adriani; Bella Syakina (Program Pascasarjana Universitas Sriwijaya, 2019)
Naturally peatlands ecosystem belongs to a stable ecosystem and tends to increase its peat thickness, but if the balance of its natural conditions is disturbed, then peatlands are easily degraded and lost altogether. The research aimed to analyze the socio-economic determinant factors causing why peatlands in South Sumatra are rapidly degraded, thus it is threatening the existence of the human life support system. The research method was using an explorative and descriptive method by making the web portal of